2008
DOI: 10.1007/s00383-008-2157-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of vitamin E and omeprazole on the hypoxia/reoxygenation induced intestinal injury in newborn rats

Abstract: Evaluation of prophylactic effects of omeprazole and/or vitamin E on the formation of free oxygen radicals (FOR) and bowel histopathology in the newborn rat model of hypoxia/reoxygenation (H/R) that resembles human necrotizing enterocolitis (NEC). Eighty newborn rats were randomly divided into eight groups. H/R was done using airtight chamber. Rats were exposed to 100% CO2 for 15 min followed by a reoxygenation for the next 15 min with 100% O2. Group 1 (n = 10) was the control group. Group 2 (n = 10) rats rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…In experimental models of NEC, administration of agents that either inhibits ROS production or acts as antioxidant has been shown to reduce tissue damage [2,3,7,8]. It was also reported that MDA increases and SOD decreases in intestinal tissue hypoxia/reoxygenation-induced intestinal injury in newborn rats [9,26,33], and our results are consistent with these previous works [4].…”
Section: Discussionsupporting
confidence: 95%
“…In experimental models of NEC, administration of agents that either inhibits ROS production or acts as antioxidant has been shown to reduce tissue damage [2,3,7,8]. It was also reported that MDA increases and SOD decreases in intestinal tissue hypoxia/reoxygenation-induced intestinal injury in newborn rats [9,26,33], and our results are consistent with these previous works [4].…”
Section: Discussionsupporting
confidence: 95%
“…Thus, it is plausible that the antioxidant properties of omeprazole may be beneficial in other pathologic conditions associated with oxidative damage (Halliwell et al, 2000;Hanauer, 2006). Omeprazole has also been shown to protect against necrotizing enterocolitis in newborn rats subjected to hypoxia/reoxygenation (Cadir et al, 2008). All of these data show that omeprazole has antioxidant and anti-inflammatory properties.…”
Section: Omeprazole Decreases Oxidant Lung Injury 111mentioning
confidence: 93%
“…roles of pro-inflammatory cytokines in the development of NEC (Seitz et al, 2005), the roles of enterocyte migration in the resolution of NEC (Cetin et al, 2004), and the protective effects of various agents including: maternal cortisol (Israel et al, 1990), intestinal trefoil factor (Guthmann and Kluthe, 2007;Shi et al, 2007), vitamin E (Cadir et al, 2008), captopril (Zani et al, 2008), polyunsaturated fatty acid supplementation , the inhibition of NF-κB (De Plaen et al, 2007), administration of pentoxifylline (Travadi et al, 2006), granulocyte colony stimulating factor (Canpolat et al, 2006), arginine (Shah and Shah, 2007) and anti-TNF-α (Halpern et al, 2006). Taken together, these studies illustrate the important role that the rat model has played in advancing our understanding of NEC pathogenesis and in devising novel therapeutic approaches for this disease.…”
Section: Clinical Puzzlementioning
confidence: 99%